Organically vs conventionally-grown dark and white chia seeds (salvia hispanica L.): Fatty acid composition, antioxidant activity and techno-functional properties - K., Alvites-Misajel (2019)
The effects of organic and conventional crop systems on chemical composition, antioxidant activity and functional properties were evaluated in white and dark chia (Salvia hispanica L.) seeds. The organic system reduced the total protein content, and increased the total carbohydrates but did not change polyunsaturated fatty acids, total phenolic or flavonoids. Organic white chia seeds showed the best techno-functional properties. The antioxidant capacity of chia extracts varied in relation to the chemical complexity and differential rate kinetics of different assays. Extractable total phenolic acids and antioxidant capacity were better in organic white chia seeds. In this first approach, we have demonstrated that the organic white chia seed has a better total antioxidant capacity measured by direct quencher approaches than its conventionally-grown counterpart. To summarize, we conclude that the organic white chia seed could be a dietary source of antioxidants with a potential to promote health benefits in systemic functions and/or microbiota and the use of its techno-functional properties for the food industry.